Estrategias comunicacionales para la prevención de consumo de drogas, en los estudiantes del ciclo básico del colegio 9 de Octubre de la ciudad de Machala, provincia de El Oro. período 2014-2015. - Rubio Roldán, Mercy Janneth (2015)
Drug use in schools has become a real problem, the fundamental purpose of this project is a develop a method of action of prevention strategies in students of the school “9 de Octubre” of Basic cycle for to prevent consumption of drugs. This being a responsible, reliable and accurate research, based on field work and taking the students themselves as key informants to identify the factors that influence drug that records the school, using instruments collecting information as interview, survey and observation, which helps us in designing strategies and methods to use. The final results concluded that the problem of the institution is drug use, so it is necessary to implement preventive strategies to prevent drug use and development of training of students.